Clinical Performance of the Spot Vision Photo Screener before and after Induction of Cycloplegia in Children - Konuralp Yakar (Journal of Ophthalmology)
Aim. To compare the clinical performance of the Spot Vision Screener used to detect amblyopia risk factors (ARFs) in children before and after induction of cycloplegia; the children were referred because they met the screening criteria of the American Association for Pediatric Ophthalmology and Strabismus (AAPOS). Methods. The Spot Vision Screener and a standard autorefractometer were used to examine 200 eyes of 100 children aged 3–10 years, before and after cycloplegia induction, in terms of ARFs. Sensitivity, specificity, and positive and negative predictive values for the detection of significant refractive errors were measured using the AAPOS referral criteria. It was explored that Spot Screener data were affected by cycloplegia. The extent of agreement between cycloplegic/noncycloplegic photoscreening data and cycloplegic autorefraction measurements was assessed using Wilcoxon and Spearman correlation analyses. Results. The Spot’s sensitivity was improved from 60.9% to 85.3% and specificity from 94.9% to 87.4% with cycloplegia compared to cycloplegic standard autorefractometer results. The positive predictive value of Spot was 75.7%, and the negative predictive value was 90.4% without cycloplegia. With cycloplegia, the positive predictive value of Spot was 63.6% and the negative predictive value was 95.8%. Conclusions. The Spot Screener afforded moderate sensitivity and high specificity prior to cycloplegia. The sensitivity and negative predictive value improved after induction of cycloplegia. Examiners should be aware of the effects of cycloplegia on their findings.